2020
DOI: 10.1002/suco.202000551
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of permeability and elastic modulus of plastic concrete containing nano silica

Abstract: Cut off walls are used under dams for the control of sub surfaces seepage and permeability of cut off wall was important. In the construction of cut off walls, plastic concrete is used and the amount of plastic concrete permeability is important. In this study, the permeability of plastic concrete was investigated and the effect of replacing nano silica instead of cement to reduce permeability was studied. So in this research, compressive strength, elastic modulus, and permeability parameters of plastic concre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, in this study, the 8% nano admixture showed more of an increased modulus of elasticity (8.5%) than other nano admixtures [12]. In another study by [28] the permeability of plastic concrete reduces as specimen ageing rises while compressive strength and elastic modulus increase. Moreover, adding nano-silica improves the concrete's compressive strength and dramatically reduces its permeability while maintaining a constant elastic modulus.…”
Section: Stress-strain Behaviour Of Concretecontrasting
confidence: 62%
“…However, in this study, the 8% nano admixture showed more of an increased modulus of elasticity (8.5%) than other nano admixtures [12]. In another study by [28] the permeability of plastic concrete reduces as specimen ageing rises while compressive strength and elastic modulus increase. Moreover, adding nano-silica improves the concrete's compressive strength and dramatically reduces its permeability while maintaining a constant elastic modulus.…”
Section: Stress-strain Behaviour Of Concretecontrasting
confidence: 62%
“…Nanomaterials are extremely small particles with a particle size of 1 to 100 nm, with high specific surface area and good volcanic ash activity [21]. Scholars have introduced nano-SiO 2 materials into the field of civil engineering, and their main applications are the improvement of concrete materials and soils [22][23][24][25]. Ahmed et al [26] incorporated nano-SiO 2 in the synthesis of geopolymer binder with red mud as the main solid source and found that nano-SiO 2 contributed to the formation of C-S-H in the geopolymer and increased the compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…There are already many practical and environmentally friendly methods to improve the durability of reinforced concrete. These methods include: changing the formulation of concrete to manufacture new types of concrete [ 4 , 5 ], coating concrete reinforcement with protective layers [ 6 , 7 ], and adding polymer modifiers [ 8 11 ], rubber [ 12 ], and minerals [ 13 , 14 ] to concrete. The use of Class F fly ash or finely ground blast furnace slag as admixtures in concrete is convenient, relatively low-cost, and environmentally friendly [ 15 ].…”
Section: Introductionmentioning
confidence: 99%